Assessment of the Priestley-Taylor coefficient and a modified potential evapotranspiration model - Georgios Nikolaou; Damianos Neocleous; Evangelini Kitta; Nikolaos Katsoulas (Smart Agricultural Technology, 2023)
The Priestley–Taylor α coefficient was adjusted to the surrounding environment in a Mediterranean greenhouse. The estimated values of α were 0.86 and 0.72 in greenhouse compartments equipped with a forced air ventilation system or wetted evaporative-pad system, respectively. The proposed α coefficient values observed were not equivalent to typical values recommended elsewhere. Furthermore, hourly sensitivity of coefficient α shows that potential evapotranspiration model computations should be applied with caution over time-intervals of a day. The validation of the proposed potential evapotranspiration model indicated a high correlation coefficient (r2=0.99) between forecast and observed cucumber evapotranspiration rates. Considering the paucity climatological data in typical plastic Mediterranean greenhouses, the proposed modified potential evapotranspiration model based on leaf temperature could be used as a practical method to optimize the irrigation scheduling.